2009
DOI: 10.1002/ange.200903946
|View full text |Cite
|
Sign up to set email alerts
|

Chemisch kontrollierte Leitfähigkeit: Torsionswinkelabhängigkeit in Biphenyldithiol‐Einzelmolekülbruchkontakten

Abstract: Stufenweise einstellbar ist die Leitfähigkeit in einer Reihe aus acht Biphenyldithiolen mit festgelegten Torsionswinkeln zwischen den Arenebenen, die synthetisiert und in einem STM‐Einzelmolekülbruchkontakt untersucht wurden. Dabei ergab sich eine cos2‐Abhängigkeit zwischen dem Torsionswinkel und der Leitfähigkeit der einzelnen Moleküle (siehe Diagramm).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 46 publications
(48 reference statements)
0
9
0
Order By: Relevance
“…It is interesting to note that the log|J| dependence with cosine square torsion angle for our biphenylthiol SAMs exhibits an opposite trend observed in similar molecules on a single-molecule scale (see the Supporting Information). [23] We attribute this to the likely weaker cohesive interaction between the SAM and top GaIn E electrode, [4] which is considered to be of van der Waals nature, being in contrast to the much stronger cova- www.chemeurj.org lent electronic coupling between the biphenyl dithiol molecules and gold electrodes studied by Vonlanthen et al [23] Electrical characterization of OTFTs with biphenylthiol-SAM functionalized electrodes: To obtain information on the charge-injection properties of OTFT electrodes modified with biphenylthiol-based SAMs, we fabricated and characterized transistors in bottom-gate bottom-contact device geometry by using P3HT as active semiconducting layer. The channel length (L) and width (W) for the OTFTs under study amounted to 10 and 10 000 mm, respectively.…”
Section: Molecular Structure [A]mentioning
confidence: 99%
See 1 more Smart Citation
“…It is interesting to note that the log|J| dependence with cosine square torsion angle for our biphenylthiol SAMs exhibits an opposite trend observed in similar molecules on a single-molecule scale (see the Supporting Information). [23] We attribute this to the likely weaker cohesive interaction between the SAM and top GaIn E electrode, [4] which is considered to be of van der Waals nature, being in contrast to the much stronger cova- www.chemeurj.org lent electronic coupling between the biphenyl dithiol molecules and gold electrodes studied by Vonlanthen et al [23] Electrical characterization of OTFTs with biphenylthiol-SAM functionalized electrodes: To obtain information on the charge-injection properties of OTFT electrodes modified with biphenylthiol-based SAMs, we fabricated and characterized transistors in bottom-gate bottom-contact device geometry by using P3HT as active semiconducting layer. The channel length (L) and width (W) for the OTFTs under study amounted to 10 and 10 000 mm, respectively.…”
Section: Molecular Structure [A]mentioning
confidence: 99%
“…Molecular structure of different BPT derivatives used. [b] Torsion angle between the planes of the phenyl rings from X-ray structure adapted from reference[23]. [c] Number of junctions formed.…”
mentioning
confidence: 99%
“…The most popular experimental strategies included the use of conducting probe atomic force microscopy and scanning tunneling microscopy [5][6][7][8][9][10][11][12][13], break junction techniques [14][15][16][17][18][19], in-wire junctions [18], mercury drop approach [20][21][22][23][24], and liquid metal eutectic Ga-In top contact [25]. A widely used approach is to study a particular series of molecules in a dedicated experiment, varying certain parameters such as the length of molecular chain [4], its conformation [26][27][28][29], character of the anchor group (groups) [13], or the work function of the substrate [7,13]. A variety of valuable information was (OPE; ˇ ≈ 0.3Å −1 [32,33]), and oligophenyls (OPh, ˇ = 0.41-0.7Å −1 [2,5,9,20,33]).…”
Section: Introductionmentioning
confidence: 99%
“…[19] An exception has also been reported; for example, it has been reported that the electron transfer between two porphyrin termini reached a minimum at the dihedral angle of 458. [20] Directly measuring the effects of the dihedral angle on electronic conductance have only been reported for a few biphenyl derivatives with amino, [21] thiol, [22] or nitrile [23] anchoring groups. All these biphenyl derivatives are very short molecules with a molecular length around 1 nm.…”
Section: Introductionmentioning
confidence: 99%
“…The designed molecular wires consist of two phenyl-ethynylphenyl p units that have a length of 2.5 nm, which is more than two times the length of the biphenyl molecules studied previously. [21][22][23] The repulsion of methyl groups in the ortho position to the biphenylic C À C link induces a dihedral angle between the two terminal p units. It is expected that the number of À CH 3 units dictates the dihedral angle and decreases the conformational variation of each molecule immobilized in the junction.…”
Section: Introductionmentioning
confidence: 99%